Praktik "Teaching English" Mahasiswa Program Studi Tadris Bahasa Inggris Melalui Program Praktik Lapangan di MA AL Fatah Badas - Novi Rina Dewi; Yasminto, Muhammad (JIK-PkM: Jurnal Inovatif dan Kreatif hasil Pengabdian kepada Masyarakat, 2024)
PPL is a practical program that aims to develop professional students by applying their knowledge, attitudes, and skills. This program requires students to integrate their previous learning experiences into teaching activities and other tasks in order to gain practical experience in managing an educational institution. Through this program, students have the opportunity to directly engage with the conditions of an educational institution and gain new experiences that complement their theoretical knowledge. The goal of this teaching practice program can give some advantages for the students, the MA Al-Fatah institutions, and the Islamic Institute of Hasanuddin Pare. This research is conducted through a field study by using a qualitative descriptive method, which involves describing research of the data through word explanations. The data is collected through observations and teaching activities carried out by students of the English Tadris study program. The practical Field Experience of Islamic Institue of Hasanuddin Pare 2022-2023 is done on December 6th 2022 – February 4th 2023 at Islamic Senior High School Al –fatah Badas Pare.